Memoryless linearity in undoped and B-doped graphene FETs: A relative investigation to report improved reliability. (October 2021) - Chandrasekar, L.; Pradhan, K.P.
Abstract: In this work, reliability of boron-doped graphene field effect transistor (GFET) is examined by modeling the effect of doping in terms of linearity performance metrics. The key potential ( V N ) induced in B doped GFET is analytically modeled for various B doping concentrations. An accurate compact equivalent circuit model integrated with V N for B doped GFET is proposed to investigate the effects of memoryless nonlinearity on transconductance. The proposed equivalent circuit model is verified with the simulated results of an industry standard circuit simulation tool. The fundamental figures of merit (FOMs) such as second and third order harmonic distortion terms ( HD 2 and HD 3 ), gain compression point ( A in, 1 dB ), second and third order intermodulation distortion terms ( IM 2 and IM 3 ), second and third order input intercept points ( A IIP 2 and A IIP 3 ) are mathematically modeled for doped GFET to examine the linear behaviour of the device. In addition to that, these FOMs are investigated with respect to various B doping concentrations, applied small signal amplitude, and gate-oxide capacitance. The proposed model is compatible and predicting accurate results for both B doped and undoped GFET. The simulation results are having excellent agreement with the mathematical model, which are also compared with undoped GFET and conventional MOSFET. It is also noticed that by doping the graphene sheet with boron significantly induces bandgap in it and hence enhances the linear behaviour of the B doped GFET. Hence, reliability of doped GFET is improved while comparing with undoped GFET and promises highly desirable linearity requirement in analog/RF applications.